Comprehensive analysis of serum cytokines in patients with multiple myeloma before and after lenalidomide and dexamethasone - Takuto Tachita; Masaki Ri; Sho Aoki; Arisa Asano; Takashi Kanamori; Haruhito Totani; Shiori Kinoshita; Yu Asao; Tomoko Narita; Ayako Masaki; Asahi Ito; Shigeru Kusumoto; et al. (Cancer Medicine)
Abstract Multiple myeloma (MM) is an incurable B‐cell malignancy often accompanied by profound immunodeficiency. Lenalidomide (Len) is an immunomodulatory drug that exerts promising therapeutic effects on MM through the immune system. However, predictive markers related to the effects of Len treatment are not fully understood. This study aimed to identify candidate biomarkers for predicting the clinical efficacy of Len and dexamethasone (Ld) therapy through a comprehensive analysis of serum cytokines. The levels of 48 cytokines in the serum of patients with MM just before Ld therapy (n = 77), at the time of best response (n = 56), and at disease progression (n = 49) were measured and evaluated. Patients with high IL‐18 and M‐CSF levels showed significantly shorter progression‐free survival and overall survival (OS). In contrast, patients with high PDGF‐BB levels had longer survival. Moreover, low levels of G‐CSF, IL‐7, IL‐8, and SDF‐1α were associated with shorter OS after Ld therapy. During Ld therapy, pro‐inflammatory cytokines such as IL‐2Rα, IL‐18, and TNF‐α were decreased, while IFN‐γ was increased. IL‐4 and IL‐6 levels increased during disease progression. In conclusion, this study provides a better understanding of the association between cytokines and the efficacy of Ld therapy as well as the unique changes in cytokines related to inflammatory and immune responses during Ld therapy.